2021
DOI: 10.24996/ijs.2021.62.11(si).9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of Spiral Solar Water Heater Using Iron Plate/Sand Absorber for Domestic Use

Abstract: The sun which is all energy sources, in today's society, hot water is used for various purposes starting from household to power production. People are adopting various ways to accomplish these goals, such as firewood heat and electrical power, so solar energy is an alternative to the dwindling resources of fossil fuels. Conversion of solar radiation into heat is one of the simplest and most direct applications of this energy, it can be used to heat water systems. A widely used flat-plate solar collector. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Gumus investigated experimentally the effect of different biodiesel blends (B5, B20, B50, and B100) on fuel injection pressures (18, 20, 22, and 24 MPa) in a naturally aspirated, single cylinder, air cooled, DI diesel engine, with a focus on BSFC and exhaust gas emissions [12][13][14][15][16]. The results were obtained at engine speeds of 2100 rpm at various engine loads and revealed an increase in BSFC of biodiesel blends (B20, B50, and B100) as injection pressure was increased [17][18][19][20]. When using biodiesel at higher injection pressure, CO, UHC, and smoke opacity were reduced, while CO2 beside to NOx emanations enlarged.…”
Section: Introduction 11 Biodiesel Fuelmentioning
confidence: 99%
“…Gumus investigated experimentally the effect of different biodiesel blends (B5, B20, B50, and B100) on fuel injection pressures (18, 20, 22, and 24 MPa) in a naturally aspirated, single cylinder, air cooled, DI diesel engine, with a focus on BSFC and exhaust gas emissions [12][13][14][15][16]. The results were obtained at engine speeds of 2100 rpm at various engine loads and revealed an increase in BSFC of biodiesel blends (B20, B50, and B100) as injection pressure was increased [17][18][19][20]. When using biodiesel at higher injection pressure, CO, UHC, and smoke opacity were reduced, while CO2 beside to NOx emanations enlarged.…”
Section: Introduction 11 Biodiesel Fuelmentioning
confidence: 99%
“…The experimental study determined that selecting the right material of manufacture for burner is important for moderating air pollutants from combustion of LPG and enhance air quality greatly. They found that the burners made of cast iron and brass have emission indices which satisfactory standard limit by International Organization for Standardization and other regulations [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…But the process of erosion occurs due to chemical or physical forces [22][23][24][25][26][27]; for example, the erosion of rocks occurs due to rainwater falling on them. In short, the erosion process may occur as part of the erosion process but the erosion process cannot occur as a result of the erosion [28][29][30][31][32] as appearance in Figure 1.…”
Section: Introductionmentioning
confidence: 99%